Implementasi Model Pembelajaran STAD terhadap Keterampilan Argumentasi, Aktivitas, dan Respon Siswa pada Materi Keanekaragaman Hayati Terintegrasi Nilai-Nilai Keislaman - Zia Safinatun Naza; Asrianty Mas'ud; Meti Maspupah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the implementation of the Student Teams Achievement Divisions (STAD) learning model in improving students’ argumentation skills, learning activities, and responses on biodiversity topics integrated with Islamic values. This research employed a quasi-experimental method with a non-equivalent control group design, involving an experimental class applying STAD and a control class using conventional instruction. The instruments used included an argumentation skills test, learning implementation observation sheets, and student response questionnaires. The results indicate that learning implementation in the experimental class reached an average of 88% for teachers and 89% for students, while the control class achieved 82% and 80%, respectively, both categorized as good. Improvement in argumentation skills in the experimental class is shown by an increase in the average score from 62.56 to 82.08 with an N-Gain of 0.51 (moderate), whereas the control class increased from 58.77 to 71.48 with an N-Gain of 0.26 (low). The posttest hypothesis test revealed a significant difference with a Sig. value of 0.002, supported by an effect size of 0.87, classified as large. Student responses toward STAD reached an average of 68.31% (fair), higher than the control class at 65.78%Thus, the implementation of STAD integrated with Islamic values is proven effective in enhancing students’ argumentation skills.